THE VALUE OF SERUM-ASCITES ALBUMIN GRADIENT AS A PREDICTOR OF SPONTANEOUS BACTERIAL PERITONITIS IN PATIENTS WITH LIVER CIRRHOSIS AND ASCITES - Lichoska Josifovikj, Fana; Grivcheva Stardelova, Kalina; Todorovska, Beti; Andreevski, Vladimir; Nikolov, Filip; Adem, Dzem (My University, 2022)
Due to the high risk of adverse outcome, identifying predisposing factors for spontaneous bacterial peritonitis (SBP) is of paramount importance. Serum ascites albumin gradient (SAAG) has recently been included in the recommendations for the management of ascites in patients with cirrhosis by some associations. ; Aim - to determine the value of SAAG as a predictor of SBP and to compare the average values of SAAG in patients with SBP and non-SBP.; The study was designed as a prospective-analytical-observational and was conducted at the University Clinic for Gastroenterohepatology in Skopje in one-year period. The study population included 70 patients hospitalized patients with established liver cirrhosis, regardless of etiology They were divided into two groups, 35 patients with SBP and 35 non-SBP, with similar demographic characteristics as the SBP group with sterile ascites, in which all variables were examined as in the study group. The selection of patients who were included in the study was conducted according to predetermined inclusion and exclusion criteria.; The average value of SAAG in SBP was 19.0±4.6, and in non-SBP it was higher (23.2±5.5). The difference between the mean values was statistically significant for p<0.05 (t-test = 3.46512; p=0.000992). The univariate analysis of SAAG in prediction of SBP showed that SAAG <20 g/L significantly increased the chance of SBP by five times (Exp (B) = 5.337 (CI (1.976-15.516)).; Our analysis registered a statistically significant difference between the average values of SAAG in both groups. SAAG is a good predictor, significantly associated with the occurrence of SBP. Additional and extensive studies are necessary in order to confirm our conclusion in the future.
Keywords: Spontaneous bacterial peritonitis (SBP); serum ascites albumin gradient (SAAG)